Pengaruh Kualitas Produk Terhadap Loyalitas Pelanggan Kosmetik Wardah di Transmart Bahu Manado - Nyonyie, Riska Asnawi; Kalangi, Johnny A. F.; Tamengkel, Lucky F. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to determine the effect of Product Quality on Customer Loyalty Wardah Cosmetic at Transmart Bahu Manado. This research method uses a quantitative method, with a sample of 96 respondents who are Wardah product costumers. The sampling techniques in this study are using Purposive Sampling. Data collection techniques in this study were questionnaires. The data analysis method used in this study is a simple regression data analysis method with an associative approach to see a causal relationship that includes validity test, reliability test, and simple regression analysis processed using the help of computer program SPSS 25. From the test result can be known statistically, it can be seen clearly that the independent variable Product Quality affects the dependent variable Customer Loyalty. The result of the study show: Based on the calculation results of the determinant coefficient obtained the R square value of 0,725 or 72,5% which states that there is variable influence Product Quality on the variable Customer Loyalty, while the remaining 24,5 % is influenced by other factors not present in this study. This shows that Product Quality has a significant effect on Customer Loyalty. Where if the Product Quality is getting better, Customer Loyalty will be higher too.